FLEXIBILITY IN CHILDREN WITH DOWN SYNDROME (Fiep Bulletin - online, 2015)
moderate flexibility presents relation with the health, however extreme of range of motion they are not recommended for the population in general for the instability risk  in muscle and joints.  The hiperflexibility can be related, in accordance with literature, to the pathologies as the Down Syndrome (SD).  Objective:  this study it compared the indices of flexibility of carrying children of Down Syndrome, with said children normal.  Method:  this research was of the descriptive type of case has controlled, being carried through with 12 children between 5 and 7 years of age, subdivided in 2 groups:  group 1 (SD), composition for 6 children of both sex, carriers of  Down Syndrome;  e group 2 (CN), with 6 said children normal, also of both sex.  The measurements had been carried through  the composed flexitest for 20 movements, in the period of the morning, without previous accomplishment of heating.  Results:  in 19 movements, being exception the movement of posterior shoulder aduction  with 180° of abduction, group SD presented superior flexibility (p
Keywords: flexibility; child; hiperflexibility; Down Syndrome.